Analisis Sistem Pengendalian Intern Penjualan Kredit PT. Medisia Sainsindo Dengan Standar COSO - Harahap, Romi Rianto; Anrizal, Sry Yullia; Masdihen, A Agim (JCA (Jurnal Cendekia Akuntansi), 2023)
This research aims to determine the internal control system for credit sales implemented by PT. Medisia Sainsindo has fulfilled the components contained in the Committee of Sponsoring Organizations (COSO). Based on the research results, it can be seen that the internal control system for credit sales of PT. Medisia Sainsindo almost meets COSO standards. 93% of the environmental control component has been implemented. 80% of the risk assessment component has been carried out. 92% of the control activity components have been carried out effectively. The information and communication component has been implemented 100%. 83% of the monitoring component has been implemented.